Culture is a luxury in Latin America - Acerenza, Santiago; Gandelman, Néstor (Estudios de Economía, 2019)
In this paper we use micro-data from income and expenditure surveys for seven Latin American countries. We estimate Engel equations and present stylized facts regarding cultural spending. Culture activities are a key indicator of a society development and therefore cultural spending decisions are illustrative of how individuals behave and interact within society. We find that culture behaves as a luxury good with income (expenditure) elasticities of cultural spending around 2. Further, we estimate elasticities for three components of cultural spending: spending in cinemas, theaters, music and dancing performances, spending in sports events and spending in other cultural activities. These expenditure elasticities are remarkably similar, also near 2. Additionally, we find that cultural spending is larger in urban areas, larger for households where the household head is a female and larger in household with more members but lower per child as the number of children increases. We find that cultural spending is positively correlated with the education level of the household head and that older household heads allocate a lower share of the budget to culture.